2015
DOI: 10.1007/s40259-015-0132-7
|View full text |Cite
|
Sign up to set email alerts
|

How Much Are Biosimilars Used in Clinical Practice? A Retrospective Italian Population-Based Study of Erythropoiesis-Stimulating Agents in the Years 2009–2013

Abstract: PurposeTo explore the prescription patterns of erythropoiesis-stimulating agents (ESAs) in four large Italian geographic areas, where different health policy interventions to promote biosimilar use in routine care are undertaken.MethodsA retrospective drug utilization study was conducted during the years 2009–2013. The data sources were the administrative databases of the Tuscany region and of the Caserta, Palermo, and Treviso Local Health Units (LHUs). The characteristics, prevalence, and switching patterns o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 6 publications
(7 reference statements)
2
54
0
Order By: Relevance
“…Incentive policies applied to biosimilars are heterogeneous across countries. At the time of the review, pharmaceutical prescription budgets or prescription quotas were reported in place for half of the countries [14,19,[39][40][41][42][43] Financial incentives or penalties measures were found in countries applying pharmaceutical prescription budgets and/or prescription quotas, but were reported as not frequently enforced (Belgium, Germany) or enforcement was not documented in the literature (Greece, Italy, Sweden, the UK) [14,39,41,42,44] Except for Poland, where switching by the physician is generally encouraged [45][46][47], some countries (Belgium, France, and Italy) do not recommend switching even if they do not prohibit it [14,39], while some other countries might recommend it in some specific cases (e.g., products with same producer (Germany, Sweden) [14], sufficient elapse time between two treatments, or in case of treatment failure (Hungary) [46,47]. In Spain, patients who started biologic therapy usually continue to receive the same medicine, and all decisions should be taken by physicians [13].…”
Section: Resultsmentioning
confidence: 99%
“…Incentive policies applied to biosimilars are heterogeneous across countries. At the time of the review, pharmaceutical prescription budgets or prescription quotas were reported in place for half of the countries [14,19,[39][40][41][42][43] Financial incentives or penalties measures were found in countries applying pharmaceutical prescription budgets and/or prescription quotas, but were reported as not frequently enforced (Belgium, Germany) or enforcement was not documented in the literature (Greece, Italy, Sweden, the UK) [14,39,41,42,44] Except for Poland, where switching by the physician is generally encouraged [45][46][47], some countries (Belgium, France, and Italy) do not recommend switching even if they do not prohibit it [14,39], while some other countries might recommend it in some specific cases (e.g., products with same producer (Germany, Sweden) [14], sufficient elapse time between two treatments, or in case of treatment failure (Hungary) [46,47]. In Spain, patients who started biologic therapy usually continue to receive the same medicine, and all decisions should be taken by physicians [13].…”
Section: Resultsmentioning
confidence: 99%
“…In Italy, several regional provisions related to biosimilars regulate biologic prescription and expenditure targets. For example, (1) in the Campania and Umbria regions, the main objective is to achieve a biosimilar utilization rate at least equal to the number of naïve patients, whereas in the Veneto region, the dispensed packages of biosimilars must constitute at least 60% of all dispensed packages of G-CSF, EPO, or hGH; (2) in Sicily, Veneto, Campania, and Tuscany, drug-naïve patients must be treated with cheaper biosimilars, and when patients are switched, the lower cost medicine should be chosen; any deviations from these rules should be justified by the prescriber [57][58][59][60]. In Sweden, county councils set quotas and target budgets for hospitals, applicable to various therapeutic classes, including biosimilars.…”
Section: Demand-side Policies For Biosimilarsmentioning
confidence: 99%
“…Germany, Italy [58,59], and Belgium) or potential financial rewards for physicians who meet their targets (e.g. Italy [6], Sweden, some Spanish regions, and the UK [63,64]).…”
Section: Demand-side Policies For Biosimilarsmentioning
confidence: 99%
See 2 more Smart Citations